Barriers and facilitators to adopting high value practices and de-adopting low value practices in Canadian intensive care units: a multimethod study. Issue 3 (15th March 2019) - Sauro, Khara; Bagshaw, Sean M; Niven, Daniel; Soo, Andrea; Brundin-Mather, Rebecca; Parsons Leigh, Jeanna; Cook, Deborah J; Stelfox, Henry Thomas
Abstract : Objective: To compare and contrast illustrative examples of the adoption of high value practices and the de-adoption of low value practices. Design: (1) Retrospective, population-based audit of low molecular weight heparin (LMWH) for venous thromboembolism (VTE) prophylaxis (high value practice) and albumin for fluid resuscitation (low value practice) and (2) cross-sectional survey of healthcare providers. Setting: Data were collected from nine adult medical-surgical intensive care units (ICUs) in two large Canadian cities. Patients are managed in these ICUs by a group of multiprofessional and multidisciplinary healthcare providers. Participants: Participants included 6946 ICU admissions and 309 healthcare providers from the same ICUs. Main outcome measures: (1) The use of LMWH for VTE prophylaxis (per cent ICU days) and albumin for fluid resuscitation (per cent of patients); and (2) provider knowledge of evidence underpinning these practices, and barriers and facilitators to adopt and de-adopt these practices. Results: LMWH was administered on 38.7% of ICU days, and 20.0% of patients received albumin. Most participants had knowledge of evidence underpinning VTE prophylaxis and fluid resuscitation (59.1% and 84.2%, respectively). Providers perceived these practices to be followed. The most commonly reported barrier to adoption was insufficient knowledge/understanding (32.8%), and to de-adoption was clinical leader preferences (33.2%). On-site education was the most commonly identified facilitator for adoption and de-adoption (67.8% and 68.6%, respectively). Conclusions: Despite knowledge of and self-reported adherence to best practices, the audit demonstrated opportunity to improve. Provider-reported barriers and facilitators to adoption and de-adoption are broadly similar.